Loss Analysis of Post-Harvest Management System of Phoenix Oyster Mushroom in Nakhon Pathom Province. - Chanasuk, Kasamon; Koprasert, Kanokpatch; Ditsathaporncharoen, Santi; Sukcharoenpong, Sompon (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research attempted to analyze the loss of post-harvest management system of supply chain of Phoenix Oyster Mushroom industry in Nakhon Pathom province. Samples used in the study were selected by purposive sampling. They consisted of two farmers growing Phoenix Oyster Mushroom in normal house and in EVAP house. Research instruments were questionnaires and laboratory records. Data were collected by measuring weight and firmness of the mushroom after harvest. Percentage, mean, and standard deviation were used for data analysis. After analyzing the loss of post-harvest of Phoenix Oyster Mushroom, it was found that the physical loss of the mushroom grown in normal house was caused by the destruction of mushroom weeds. As a result, the mushroom had not perfect shapes and there were more fungal and bacterial contamination than the mushroom grown in EVAP house since the EVAP house had a better and more appropriate control system. In addition, when analyzing weight and firmness loss of the mushroom after harvest, it was found that the mushroom yields from the normal house had higher loss of weight and firmness than those from the EVAP house. Moreover, the results of weight and firmness loss analysis of the mushroom after transportation to Pathom Mongkol and Sri Muang markets showed that the mushroom on the first shelf had the highest weight loss, whereas the mushroom on the third shelf had the highest loss of firmness. Furthermore, it was found that the mean of weight and firmness loss after transportation to Sri Muang market was higher than transportation to Pathom Monglok market. Article history : Received 24 December 2017 Revised 12 May 2018 Accepted 20 May 2018 SIMILARITY INDEX = 0.00